Effects of an employer-based intervention on employment outcomes for youth with significant support needs due to autism. (April 2017) - Wehman, Paul; Schall, Carol M; McDonough, Jennifer; Graham, Carolyn; Brooke, Valerie; Riehle, J Erin; Brooke, Alissa; Ham, Whitney; Lau, Stephanie; Allen, Jaclyn; Avellone, Lauren
The purpose of this study was to develop and investigate an employer-based 9-month intervention for high school youth with autism spectrum disorder to learn job skills and acquire employment. The intervention modified a program titled Project SEARCH and incorporated the use of applied behavior analysis to develop Project SEARCH plus Autism Spectrum Disorder Supports. A randomized clinical trial compared the implementation of Project SEARCH plus Autism Spectrum Disorder Supports with high school special education services as usual. Participants were 49 high-school-aged individuals between the ages of 18 and 21 years diagnosed with an autism spectrum disorder and eligible for supported employment. Students also had to demonstrate independent self-care. At 3 months post-graduation, 90% of the treatment group acquired competitive, part-time employment earning US$9.53–US$10.66 per hour. Furthermore, 87% of those individuals maintained employment at 12 months post-graduation. The control group's employment outcomes were 6% acquiring employment by 3 months post-graduation and 12% acquiring employment by 12 months post-graduation. The positive employment outcomes generated by the treatment group provide evidence that youth with autism spectrum disorder can gain and maintain competitive employment. Additionally, there is evidence that they are able to advance within that time toward more weekly hours worked, while they also displayed increasing independence in the work setting.